An atypical lipomatous tumor mimicking a giant fibrovascular polyp of the hypopharynx: A case report. Issue 43 (October 2017) - Ioanidis, Khrystyna E.; MacNeil, Stephanie Danielle; Tay, Keng Yeow; Wehrli, Bret
Abstract: Rationale: Giant fibrovascular polyps (GFVPs) found in the hypopharynx are exceedingly rare. These are benign tumors which are identified by CT or MRI and usually treated based on symptoms. Even more rarely, pathology may identify one of these masses as an atypical lipomatous tumor (ALT). This paper will present a case of an ALT of the hypopharynx that was originally classified as a GFVP, highlighting the difficulty in distinguishing between them and the importance of making the correct diagnosis. Patient Concerns: An 84-year-old man presented to the emergency department with a 6-month history of a pedunculated hypopharyngeal growth, dysphagia, and intermittent dyspnea. Diagnoses: The mass was characterized as a GFVP by barium swallow and MRI. Interventions: The hypopharyngeal mass was resected for obstructive symptoms and to confirm the diagnosis. Final pathology found the mass to be more consistent with an atypical lipomatous tumor (ALT). Outcomes: The patient's dysphagia and dyspnea resolved. He was free of recurrence at 22 months postoperative. Lessons: Both GFVPs and ALTs are very rarely found in the hypopharynx but can be easily misclassified as one another. Imaging is useful to initially characterize the mass, but to definitively differentiate between them, pathological analysis is necessary. Although they are rare, it is important to consider both possibilities on the differential for hypopharyngeal masses. Further, accurate analysis is essential to distinguish between them because their definitive management and follow-up is different.